A Novel Mouse Model of MYO7A USH1B Reveals Auditory and Visual System Haploinsufficiencies - Calabro, Kaitlyn R.; Boye, Sanford L.; Choudhury, Shreyasi; Fajardo, Diego; Peterson, James J.; Li, Wei; Crosson, Sean M.; Kim, Mi-Jung; Ding, Dalian; Salvi, Richard; Someya, Shinichi; Boye, Shannon E. (Frontiers in Neuroscience, 2019)
Usher’s syndrome is the most common combined blindness-deafness disorder with USH1B, caused by mutations in MYO7A, resulting in the most severe phenotype. The existence of numerous, naturally occurring shaker1 mice harboring variable MYO7A mutations on different genetic backgrounds has complicated the characterization of MYO7A knockout and heterozygote mice. We generated a novel MYO7A knockout mouse (Myo7a-/-) that is easily genotyped, maintained, and confirmed to be null for MYO7A in both the eye and inner ear. Like USH1B patients, Myo7a-/- mice are profoundly deaf, and display near complete loss of inner and outer cochlear hair cells. No gross structural changes were observed in vestibular hair cells. Myo7a-/- mice exhibited modest declines in retinal function but, unlike patients, no loss of retinal structure. We attribute the latter to differential expression of MYO7A in mouse vs. primate retina. Interestingly, heterozygous Myo7a+/- mice had reduced numbers of cochlear hair cells and concomitant reductions in auditory function relative to Myo7a+/+ controls. Notably, this is the first report that loss of a single Myo7a allele significantly alters auditory structure and function and suggests that audiological characterization of USH1B carriers is warranted. Maintenance of vestibular hair cells in Myo7a-/- mice suggests that gene replacement could be used to correct the vestibular dysfunction in USH1B patients. While Myo7a-/- mice do not exhibit sufficiently robust retinal phenotypes to be used as a therapeutic outcome measure, they can be used to assess expression of vectored MYO7A on a null background and generate valuable pre-clinical data towards the treatment of USH1B.